2022
DOI: 10.22495/jgrv11i1siart14
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting female online purchase decision

Abstract: This study enhances the existing literature on female online buying decisions by evaluating the factors shaping women’s clothing purchase decision-making. Hence, it investigates the influence of social media interactive marketing activities, i.e., electronic advertising (e-Ads), electronic word of mouth (e-WOM), interaction (Int.), and content credibility (CC), on female purchase decisions. The study adopted the logic of quantitative approach using an e questionnaire as a main data collection tool targeting on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Finally, the literature has reported that demographic factors, including both gender and age, impact how individuals respond to the use of technology devices. For instance, female users are more likely to buy travel goods offered by travel apps and to recommend them to others, while male users are more careful in their purchases and recommendations (Allan et al, 2022). Also, a decent job with a high monthly income might increase spending, and vice versa (Mancino et al, 2018).…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Finally, the literature has reported that demographic factors, including both gender and age, impact how individuals respond to the use of technology devices. For instance, female users are more likely to buy travel goods offered by travel apps and to recommend them to others, while male users are more careful in their purchases and recommendations (Allan et al, 2022). Also, a decent job with a high monthly income might increase spending, and vice versa (Mancino et al, 2018).…”
Section: Hypotheses Developmentmentioning
confidence: 99%